A Case of Advanced Glaucoma with Increased Episcleral Venous Pressure in a 17-Year-Old with Eisenmenger Syndrome. (23rd October 2017) - Grech, Leanne; Mifsud, Adrian; Caruana, Maryanne; Carbonaro, Francis
Abstract : Eisenmenger syndrome refers to reversal of shunt and central cyanosis due to pulmonary hypertension induced by congenital heart disease with a large systemic-to-pulmonary shunt. We report a case of a 17-year-old man with Eisenmenger syndrome who presented with gradual deterioration in visual acuity and was diagnosed with advanced secondary open angle glaucoma. There have been reports of patients suffering from thrombosis due to hyperviscosity associated with this syndrome; however, to our knowledge, the association of secondary open angle glaucoma with Eisenmenger syndrome has not yet been documented.